The Influence Concept Attainment Learning Model on Students Argumentative Skills and Concepts Understanding on Angiosperm Material - Fadhil Ramdhani; Purwati Kuswarini Suprapto; Mufti Ali (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2023)
Students need their own arguing skills in learning process. Based on the observation, it is known that not all students have the same courage to express their opinions, both verbally and written. This leads to a lack of understanding of the media design content being studied by education participants. The application of the Concept Attainment learning model is expected to train students how to construct their own concepts and be able to express them verbally. This study aims to determine the effect of concept attainment learning model on students' argumentative skills and concept understanding of angiosperms subject in class X MIPA SMAN 5 Tasikmalaya. This study used a quasi-experimental research method with a research design Nonequivalent Control Group Design. The population in this study were all students of X MIPA SMAN 5 Tasikmalaya of seven classes with a total number of 245 students. The sampling technique used was purposive sampling, with the samples used class X MIPA 3 as the experimental class and X MIPA 5 as the control class with a total number of 72 students. The instruments used in this study consisted of 5 argumentative ability test questions and 10 concept understanding questions. The data analysis technique used in this research is parametric statistical data analysis technique. Data is processed by conducting prerequisite analysis in the form of a normality test, homogeneity test, and hypothesis testing using one way ANOVA test. The results showed that there was a significant effect of the concept attainment learning model on students' argumentative skills and concept understanding with a significance value of (0.000). Based on these positive results, it can be used as a reference for educators to use concept attainment models that support teaching and learning activities.